Trace metal concentrations and antioxidant activities of Tripleurospermum parviflorum and Tripleurospermum tenuifolium - Fafal, Tugce (Progress in Nutrition, 2022)
In this study, we determined the trace element contents of Tripleurospermum parviflorum and T. tenuifolium from Izmir, Turkey. The complete phenolic and flavonoid contents, as well as the antioxidant properties of methanol extracts of Tripleurospermum parviflorum and T. tenuifolium aerial parts, were also examined.  Nine minerals (Na, Ca, Mg, K, Si, Al, P, S and Ti), six trace elements (Fe, Zn, Ni, Br, Ag and Ta) were determined. The heavy metal content in percentages were determined as 9.78-11.08% and 21.63-19.94% for powdered drug and water extracts of Tripleurospermum parviflorum and T. tenuifolium, respectively. K was found the highest concentration in T. tenuifolium water extract was found to posses highest concentration of K. In addition, Na, Cl and Ca were also obtained in significant amounts in water extracts of two species. The presence of K and Ca in two Tripleurospermum species explain the traditional use of these drugs against cardiac disorders. The methanolic extract of T. parviflorum demonstrated the higher antioxidant activity than T. tenuifolium. The antioxidant activity assay findings were found to be in a strong correlation with the total phenolics and flavonoid content of the extracts.